2012
DOI: 10.1097/bpo.0b013e3182619181
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 3-Tesla Magnetic Resonance Imaging for the Diagnosis of Intra-articular Knee Injuries in Children and Teenagers

Abstract: Diagnostic study--Level 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…After the inclusion criteria were applied, 21 articles were eligible for inclusion. Eight studies were removed due to the exclusion criteria (no full text or translation in the English language, n = 3 articles; use of non-3-T MRI, n = 3; inability to use results because of inappropriate methods, n = 1; and review article of different 3-T MRI protocols, n = 1), resulting in 13 studies included for the final review [32][33][34][35][36][37][38][39][40][41][42][43][44]. Table 1 shows the results of the QUADAS-2 tool for the 13 studies: Seven studies scored 11 points or 100% [33,[36][37][38][39][40]42], four studies scored 10 points or 91% [32,35,43,44], and two studies scored 9 points or 82% [34,41].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the inclusion criteria were applied, 21 articles were eligible for inclusion. Eight studies were removed due to the exclusion criteria (no full text or translation in the English language, n = 3 articles; use of non-3-T MRI, n = 3; inability to use results because of inappropriate methods, n = 1; and review article of different 3-T MRI protocols, n = 1), resulting in 13 studies included for the final review [32][33][34][35][36][37][38][39][40][41][42][43][44]. Table 1 shows the results of the QUADAS-2 tool for the 13 studies: Seven studies scored 11 points or 100% [33,[36][37][38][39][40]42], four studies scored 10 points or 91% [32,35,43,44], and two studies scored 9 points or 82% [34,41].…”
Section: Resultsmentioning
confidence: 99%
“…2). The Schub et al [44] study was the only exception. In that study, bias with regard to the index test was unclear ( Fig.…”
Section: Methodologic Assessmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Possible explanations include the fact that the meniscal injury can occur between the MRI and the surgery as a result of the knee instability or it has also been suggested that severe soft tissue disruption can affect visualization of the meniscus [18]. In this study, a 1.5 T MRI scanner was used; however, there is some evidence that using a high-field-strength magnet 3.0 T MRI scanner may improve diagnostic accuracy in ligament and meniscal injuries [21,[23][24][25]. Due to the importance of diagnostic accuracy for surgical planning in patients with knee dislocation, evaluation of accuracy of the 3.0 T scanner may be useful.…”
Section: Discussionmentioning
confidence: 99%